Analisis Kemampuan dan Pengetahuan Keamanan Siber untuk Kompetisi Capture the Flag - Jean Tirstan T; Joy Gilbert A; Nelmiawati Nelmiawati (Politeknik Negeri Batam, 2022)
CTF (Capture The Flag) competitions have emerged as a pivotal instrument in development of cyber security education over the past six years. It is imperative to ensure that the CTF competitions continue to develop to facilitate growth of cyber security education. To achieve the desired growth, it is necessary to analyze the progress achieved in the last six years the program has been implemented. This research collects and analyzes approximately 500 CTF solutions from the CTFtime platform. From the results of this analysis, we have identified that skills and techniques are needed in each category of CTF questions. We use the results of this analysis as a reference for questions on the CTF Platform that we created during PCT (Polibatam Cyber ​​Team) regeneration. PCT consists of a group of students from the Cyber ​​Security Engineering study program who are prepared to be at the forefront in participating in various activities related to Cyber ​​Security. The method we use is different from other CTFs, in that we use a skill-based and technique-based approach. We found that this approach was able to attract 80% of participants in solving and improving their skills in Cyber Security towards any challenges in a competitive environment.